2010
DOI: 10.1164/rccm.201001-0075oc
|View full text |Cite
|
Sign up to set email alerts
|

Role for Myeloid Nuclear Differentiation Antigen in the Regulation of Neutrophil Apoptosis during Sepsis

Abstract: These results indicate that cytoplasmic accumulation of MNDA facilitates progression of apoptosis and suggest that impaired cytoplasmic MNDA accumulation contributes to delayed neutrophil apoptosis in patients with severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 44 publications
1
58
1
Order By: Relevance
“…The latter protein category included the ␣M-␤ 2 integrin complex (CD11b/CD18) and grancalcin (50), myosin-If (51), and the CD177 neutrophil surface marker (52). The myeloid cell nuclear differentiation antigen (MNDA) manipulates neutrophil apoptosis (53). Two previous studies identified neutrophil proteins via proteomics from urethral catheter samples but did not include experiments comparing ASB patients to UTI patients (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…The latter protein category included the ␣M-␤ 2 integrin complex (CD11b/CD18) and grancalcin (50), myosin-If (51), and the CD177 neutrophil surface marker (52). The myeloid cell nuclear differentiation antigen (MNDA) manipulates neutrophil apoptosis (53). Two previous studies identified neutrophil proteins via proteomics from urethral catheter samples but did not include experiments comparing ASB patients to UTI patients (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus during apoptosis, MNDA is cleaved by caspases and then relocalises to the cytosol where it accumulates and associates with the antiapoptotic protein myeloid cell leukaemia 1 (MCL1). This leads to MCL1 degradation, resulting in apoptosis caused by mitochondrial dysfunction [12]. This relocalisation of MNDA to the cytosol is thought to be required for proper execution of apoptosis and suggests that reduced cytoplasmic accumulation of MNDA contributes to suppression of neutrophil apoptosis.…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
“…This relocalisation of MNDA to the cytosol is thought to be required for proper execution of apoptosis and suggests that reduced cytoplasmic accumulation of MNDA contributes to suppression of neutrophil apoptosis. Furthermore, in septic patients cytoplasmic accumulation and cleavage of MNDA in neutrophils was dramatically impaired [12].…”
Section: Early Research On the Human Pyhinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed apoptotic activity of peripheral blood neutrophils is observed in the course of various diseases, for example, respiratory distress syndrome in adults [25], sepsis [55][56][57][58], bacterial and viral pneumonia [59,60], exacerbation of bronchoectatic disease [61], rheumatoid arthritis [62], cystic fibrosis [63,64] and burns [65]. The correlation between the neutrophil apoptosis level and the disease severity is well established [55,58].…”
Section: Role Of Neutrophil Apoptosis In the Resolution Of Inflammationmentioning
confidence: 99%